Judith Le Soldat: Werkausgabe / Band 1: Grund zur Homosexualität Vorlesungen zu einer neuen psychoanalytischen Theorie der Homosexualität - Le Soldat, Judith (frommann-holzboog, 2015)
'Grund zur Homosexualität' opens up a radically new understanding of the psychological processes involved in the formation of what we call sexual orientation. Not only is the everyday understanding of homo- and heterosexuality questioned. Our ideas of what masculinity and femininity mean are also placed on completely new foundations. The theory that Judith Le Soldat makes available to us in this book is much more than a theory of homosexuality: It shows that a precise analysis of the phenomenon of homosexuality also provides completely new, previously unrecognized insights into the fundamental functioning of human soul allowed.